Satisfaction-induced travel: Do satisfying trips trigger more shared micro-mobility use? - Guan, Xiaodong; Israel, Fabian; Heinen, Eva; Ettema, Dick (Elsevier Ltd, 2024)
Most studies on travel satisfaction assumed it as an outcome of travel choices. However, travel choices may also be affected by people's satisfaction with travel. Ignoring this potential reverse effect will lead to an biased understanding on the link between travel behavior and subjective wellbeing. This research examined the influence of travel satisfaction on travel behavior, using questionnaire survey data on shared micro-mobility services in three European cities in 2022. The research findings suggest that travel satisfaction can serve as both pull factors and push factors of travel mode choice. A high satisfaction with shared micro-mobility trips encourages people's future use of these services. A relatively low satisfaction with daily travel also prompts the non-users to try shared bikes/e-bikes as alternative transport modes. Our research provides direct evidence on the feedback effect of travel satisfaction on travel behavior.
Keywords: Europe; Shared micro-mobility; Sustainability; Travel behavior; Travel satisfaction; Civil and Structural Engineering; Transportation; General Environmental Science